Dietary nucleotides supplementation enhances the growth and immune responses of the giant freshwater prawn, Macrobrachium rosenbergii (De Man, 1879) - Md. Belal Hossen; Md. Rokonuzzaman Kibria; Sakib Tahmid Rishan; Muhammad Tofazzal Hossain; Md. Samsul Alam (Journal of Advanced Veterinary and Animal Research)
Objective: The study aimed to assess the impact of dietary nucleotide (NT) supplementation on the growth performance and immune response of juvenile Macrobrachium rosenbergii. Materials and Methods: A commercial diet was supplemented with 0.0% (control), 0.10% (T1), 0.15% (T2), and 0.20% (T3) NT for the study. A total of 132 juvenile prawns (0.78 ± 0.03 gm) were randomly distributed into four groups, each having three replicates. Following the 75-day feeding trial, the experimental prawns were exposed to Aeromonas veronii at 8.35 × 105 colony forming unit (cfu)/ml for 7 days through a bath treatment. Results: The growth parameters and survival rate were significantly higher (p < 0.05) in NT-supplemented prawns. Immune-related parameters, e.g., total hemocyte count (THC), hemolymph protein, albumin, globulin, superoxide dismutase, and catalase activity, were also significantly higher (p < 0.05) in NT-supplemented prawns. The challenge of prawn with A. veronii resulted in a significant reduction (p < 0.05) in THC and other biochemical parameters of hemolymph and caused mortality in all the experimental groups. However, significantly higher survival (p < 0.05) against the A. veronii challenge was found in NT-supplemented prawns. Conclusion: It can be concluded that dietary NTs should be supplemented at 0.15%–0.2% to enhance the growth, immunity, and resistance of juvenile M. rosenbergii against A. veronii. [J Adv Vet Anim Res 2025; 12(2.000): 687-697]